Pengembangan Vaksin untuk Penyakit Tropis Terabaikan: Analisis Tantangan Investasi, Riset, dan Distribusi - Fajri, Mathla'il; Rindiani; Indriyani, Femi; Yulio , Vianney Gratia (Program Studi Farmasi Sekolah Tinggi Ilmu Kesehatan Sambas, 2025)
Neglected Tropical Diseases (NTDs) burden billions of individuals in developing countries, significantly impacting health and economy. While vaccination is a vital intervention, NTD vaccine development and access face multidimensional challenges related to investment, research, and distribution. This article analyzes funding gaps due to low market attractiveness and reliance on philanthropy. In research, the biological complexity of pathogens, limited infrastructure, and inadequate preclinical models pose crucial barriers. Distribution challenges include cold chain constraints, access to remote areas, and weak healthcare system capacity. Through a systematic literature review from 2004 to 2015, it was identified that these issues are interconnected, delaying vaccine availability. Dependence on public and philanthropic funding, alongside scientific and logistical complexities, hinders progress. This analysis highlights the need for stronger market incentives, increased research collaboration, development of more stable vaccine formulations, and strengthening healthcare systems to ensure equitable access. Implications for Indonesia are emphasized, highlighting the importance of research independence and strengthening distribution infrastructure.